TOWARD A THEORY OF NON-PROFIT INSTITUTIONS: AN ECONOMIC MODEL OF A HOSPITAL - Newhouse, Joseph P. (American Economic Review, 1969)
A simple model of a hospital is developed, and its implications are considered. An attempt is made to justify the realism of the model, although it cannot be entirely realistic. To develop the model the assumption is made that hospital expenses are financed by the patient and not by a third party. Thus the model may prove applicable to other non-profit institutions where third party payments are not important, such as colleges and universities, the performing arts, and museums.